Toward Prevention of Pressure Ulcer: Method of Automatic Wrinkle Removal by Friction-less Soft Robot-arm - Nakamura, Tomoyuki; Tsukagoshi, Hideyuki (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
In this study, we present a method of automatically removing wrinkles by the extension of Soft Robot-arm, focusing on the wrinkles of clothes that lead to pressure ulcers for bedridden elderlies. The proposed pneumatic driven Robot-arm is flexible in structure, capable of entering the gap between the human body and the bed surface without friction. As a result of the experiment, we confirmed that it was possible to remove wrinkles by 30% in one operation and almost 100% in three operations by extending Robot-arm in the direction to elongate wrinkles. Also, the effect of changing body pressure distribution was confirmed. Since this method can be realized with safe and simple operation, even if the caregiver is absent, it can be expected to be applied for prevention of pressure ulcers of the elderly.